2015
DOI: 10.2131/jts.40.339
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase knockout mice reveal an impact of estrogen on drug-induced alternation of murine electrocardiography parameters

Abstract: -Our in vitro characterization showed that physiological concentrations of estrogen partially suppressed the I Kr channel current in guinea pig ventricular myocytes and the human ether-a-gogo-related gene (hERG) channel currents in CHO-K1 cells regardless of estrogen receptor signaling and revealed that the partially suppressed hERG currents enhanced the sensitivity to the hERG blocker E-4031. To obtain in vivo proof-of-concept data to support the effects of estrogen on cardiac electrophysiology, we here emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
2
14
0
Order By: Relevance
“…Our study showed that the heart rate at 21 d in the CDs group was significantly higher than that of the saline group, indicating that CDs had some toxicity in the heart, a result similar to other groups' findings [31,32] . However, the heart rate of the PEG-CDs group was similar to that of the saline group, suggesting the PEGylation could considerably attenuate the heart toxicity of CDs.…”
Section: Discussionsupporting
confidence: 89%
“…Our study showed that the heart rate at 21 d in the CDs group was significantly higher than that of the saline group, indicating that CDs had some toxicity in the heart, a result similar to other groups' findings [31,32] . However, the heart rate of the PEG-CDs group was similar to that of the saline group, suggesting the PEGylation could considerably attenuate the heart toxicity of CDs.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, employment of an aromatase knockout mouse as an in vivo estrogen-null model supports the effects of estrogen on cardiac electrophysiology(Kurokawa et al , 2015). The knockout mice were generated by targeted disruption of the CYP19 gene coding aromatase cytochrome P450 (Honda et al , 1998).…”
Section: Estrogenmentioning
confidence: 99%
“…Prolongation of QT c intervals in response to the cumulative administration of E-4031 were compared between late-proestrus female mice (open circles) and aromatase knockout mice (CYP19 KO, closed circles). Modified from(Kurokawa et al , 2015). …”
Section: Figurementioning
confidence: 99%
“…; Kurokawa et al . ). During the menstrual follicular phase (prior to ovulation), oestrogen level is the highest, QT interval is longer and susceptibility to drug‐induced arrhythmias is increased.…”
Section: Introductionmentioning
confidence: 97%